Ekstrak Umbi Gadung (Diocerae hispida D) sebagai Insektisida Pembunuh Lalat di TPS Pasar Sentolo, Kulonprogo - Tuntas Bagyono; Agus Suwarni; Sigid Sudaryanto (Sanitasi: Jurnal Kesehatan Lingkungan, 2010)
Fly is one of insect vectors which can transmit microorganisms causing sto- mach diseases such as typhoid, cholera and dysentery. Tuber of Dioscerae hispida D can be used as an alternative for biological insecticide that are safer for the environment, and so that can replace the common inorganic ones which are not environmentally friendly. They study was aimed to understand the influ- ence of various concentrations of Dioscerae hispida D extract spraying towards the mortality of fly at the temporary waste disposing site of Sentolo Market of Kulonprogo, as well as to understand which concentration is the best. The study was an experiment employing post test only with control group design. Tubers of the plant were obtained from the surrounding area. The results using one-way Anova test show that the effect of various concentrations of the insecticides were significantly different (p<0,001). Since the most effective effect is gained from the 44,4% concentration, it is suggested to use this concentration for con- trolling the annoying fly. Further effect of the insecticide on other disease vec- tors such as mosquito and cockroach, may be explored.